The Geometric Mosaics at Qusayr Amra in Context - Mohammad Nassar (Greek, Roman, and Byzantine Studies, 2015)
Comparative study of the Umayyad castle’s geometric pavements shows that their creators drew on deep knowledge of Greek artistic traditions in their work for the new Muslim rulers.